Analysis of social-ecological dynamics driving conflict in linked surface-groundwater systems - (:unkn) unknown (My University, 2018)
Conflict over water resources emerges from complex interactions among biophysical, social, and economic processes operating at multiple scales. Competing use of linked surface-groundwater (LSGW) resources is an excellent yet relatively unexplored example of such conflict. Dynamic circumstances surrounding the contested installation of a high capacity municipal well in southeastern Wisconsin were examined through the theoretical lens of adaptive governance using document analysis and open-ended key stakeholder interviews. A framework analysis method extracted 16 controlling variables from the qualitative data. These controlling variables were placed on a threshold matrix at their appropriate geospatial scale (Property, Watershed, State) and process domain (Biophysical, Economic, Social), which revealed several social-ecological feedbacks not currently addressed by management authorities. Three dynamic feedback loops were identified that explain the emergence and resolution of LSGW conflict in the case study area. Conflict emerged when processes driving new development in southeastern Wisconsin threatened to impact a highly valued groundwater dependent lake. Lake groups engaged in collective learning, utilized information networks, and displayed leadership to address the issue. However, lack of participatory avenues for dispute resolution at the scale of occurrence drove lake groups to challenge the regulatory authority of the Wisconsin Department of Natural Resources (WDNR). Through order-based legitimacy, legal resolution affected governance of LSGW resources across the state, but did little to address the underlying stakeholder values driving conflict. We conclude this system will continue to be subjected to “legal back and forth,” recurrent conflict, and uncertainty for both environmental and developmental interests until a more participatory process is developed with regulatory authorities to resolve conflicts over LSGW.
Keywords: adaptive governance; conflict; linked surface-groundwater resources; resilience; social-ecological systems; thresholds